To simplify the expression \( 13^{-5} \cdot 13^{-11} \) using the properties of exponents, we can use the rule that states \( a^m \cdot a^n = a^{m+n} \).
Applying this rule, we have:
\[ 13^{-5} \cdot 13^{-11} = 13^{-5 + (-11)} = 13^{-16} \]
To express this with only positive exponents, we use the property that \( a^{-n} = \frac{1}{a^n} \):
\[ 13^{-16} = \frac{1}{13^{16}} \]
Now, we can compare this to the provided options. The equivalent expression to \( 13^{-5} \cdot 13^{-11} \) with only positive exponents is:
1 over 13^16.